Tokenism Analysis in Community Participation: A Case Study from Saung Pandu Program of Badak LNG Bontang - Sewakotama, Restra; Hamdir, Arsy A. W.; Putri, Alfah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Saung Pandu is an acronym for Usaha Unggulan Pertanian Terpadu, a Corporate Social Responsibility (CSR) program located in direct proximity to PT Badak NGL Bontang in East Kalimantan. Saung Pandu was initiated to mitigate land conflicts through community empowerment approaches. As a result, Saung Pandu has become a community development program that focuses on integrated agriculture by utilizing processed domestic wastewater from the company. This research examines the process of community empowerment and participation using the theories of empowerment and community participation. Given the intertwined nature of empowerment and participation, the empowerment process is seen as a sequence of awareness-raising, capacity building, and empowerment. Meanwhile, participation is observed through the stages of planning, implementation, benefit realization, and monitoring and evaluation. This research adopts a qualitative methodology. The findings of this study indicate that while there is an existing empowerment process, optimal participation has not been achieved. The participation that occurs is largely influenced by the historical background of conflicts between the company and the community. This is due to the segmentation of groups based on land ownership, leading to some degree of tokenism among certain parties, thereby resulting in suboptimal individual participation within the groups.